2013
DOI: 10.1159/000350084
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aquaporins in Human Embryos and Potential Role of AQP3 and AQP7 in Preimplantation Mouse Embryo Development

Abstract: Background/Aims: Water channels, also named aquaporins (AQPs), play crucial roles in cellular water homeostasis. Methods: RT-PCR indicated the mRNA expression of AQPs 1-5, 7, 9, and 11-12, but not AQPs 0, 6, 8, and 10 in the 2∼8-cell stage human embryos. AQP3 and AQP7 were further analyzed for their mRNA expression and protein expression in the oocyte, zygote, 2-cell embryo, 4-cell embryo, 8-cell embryo, morula, and blastocyst from both human and mouse using RT-PCR and immunofluorescence, respectively. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 27 publications
1
35
1
Order By: Relevance
“…It has been shown that increased expression of AQP5 occurs at the time of the embryo implantation in the rat uterus (Lindsay and Murphy 2007). Further, multiple aquaporins are expressed in the early stage human embryos and AQP3 and AQP7 may play a role in pre-implantation mouse embryo development (Xiong et al 2013). Implantation of the developing embryo in the uterus is regulated by multiple effectors, such as steroid hormones, growth factors, cytokines and cyclooxygenasederived prostaglandins , Geisert et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that increased expression of AQP5 occurs at the time of the embryo implantation in the rat uterus (Lindsay and Murphy 2007). Further, multiple aquaporins are expressed in the early stage human embryos and AQP3 and AQP7 may play a role in pre-implantation mouse embryo development (Xiong et al 2013). Implantation of the developing embryo in the uterus is regulated by multiple effectors, such as steroid hormones, growth factors, cytokines and cyclooxygenasederived prostaglandins , Geisert et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, AQP3 or ATP1B1 play an important role in blastocoel formation by regulating the accumulation of fluid. In mouse embryos, RNAi mediated knockdown of Aqp3 and Atp1b1 blocks blastocyst formation [37,38]. Altogether, these results demonstrate that maternal YAP in pig embryos promotes TE development via the regulation of key genes involved in TJ assembly and blastocoel formation.…”
Section: Discussionmentioning
confidence: 60%
“…The role of aquaporins (AQPs), water channel proteins involved in regulation of cellular water homeostasis, was studied in sea urchin, mouse, and human embryos, demonstrating their expression and implication in mammalian preimplantation embryo development (Edashige et al, 2000;Amaroli et al, 2013;Nong et al, 2013;Xiong et al, 2013). Members of the AQPs family take part in the processes of blastocyst formation as physiological mediators of fluid movement across the trophectoderm during cavitation and implantation (Cho et al, 2003;Richard et al, 2003;Watson et al, 2004).…”
Section: Mammalsmentioning
confidence: 99%